Honduras : 2016 Article IV Consultation, Third and Fourth Reviews under the Stand-By Arrangement and the Arrangement under the Standby Credit Facility-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the real output of Honduras in 2015 grew at 3.6 percent, slightly higher than projected. From the demand side, growth was supported by the recovery in private consumption-which responded positively to a reduction in gasoline prices and strong remittances inflows-and a boost in investment. On the supply side, the recovery in manufacturing and agriculture supported greater activity. The outlook for 2016 remains favorable. Real GDP through the second quarter of 2016 grew by 4.1 percent (year over year) broadly consistent with IMF staff projection of 3.6 percent for 2016. This projected growth performance is supported by scaled up public infrastructure investment and a supportive monetary policy stance.